Factors affecting the ‘Intention to shop online’: A Case Study of Indian Youth. - Dhingra, Shivam (2012)
Online Shopping is a truly remarkable innovation, which aims to bring buyers and sellers to a single boundary-less global „bazaar‟. This dissertation examines the online shopping scenario in the fast growing economy of India with respect to its Youth population. The perceptions of 45 Indian youngsters on different factors affecting online shopping were recorded by convenience sampling through a survey questionnaire, which was distributed online via the social media (Facebook). Quantitative tests including correlations and linear regressions were run on the responses of the sample in order to find the relationship between the independent (different factors) and dependent (intention to shop online) variables. The results showed a strong and positive correlation between TAM factors, Trust, Reliability, Website Features, Prior e-shopping experience, Information Satisfaction, Previous Internet Experience, E-service Quality and Self-efficacy and the Intention to Shop Online. Linear regressions found a good variation caused by all factors on intention to shop online in the mentioned order, with highest variation recorded for self-efficacy on Indian Youth‟s intention to shop online. Most importantly; it was found that the Indian youth were cautious and price-savvy in nature. Furthermore, they highly valued the social presence of a website.